Mental health in biological disasters: From SARS to COVID-19. (August 2021) - Hsieh, Kuan-Ying; Kao, Wei-Tsung; Li, Dian-Jeng; Lu, Wan-Chun; Tsai, Kuan-Yi; Chen, Wei-Jen; Chou, Li-Shiu; Huang, Joh-Jong; Hsu, Su-Ting; Chou, Frank Huang-Chih
Background: The outbreak of coronavirus disease 2019 (COVID-19), like severe acute respiratory syndrome (SARS), provokes fear, anxiety and depression in the public, which further affects mental health issues. Taiwan has used their experience of the SARS epidemic for the management of foreseeable problems in COVID-19 endemic. Aim/Objective: This review summarizes issues concerning mental health problems related to infectious diseases from current literatures. Results: In suspected cases under quarantine, confirmed cases in isolation and their families, health care professionals, and the general population and related effective strategies to reduce these mental health issues, such as helping to identify stressors and normalizing their impact at all levels of response as well as public information and communication messages by electronic devices. The importance of community resilience was also addressed. Psychological first aid, psychological debriefing, mental health intervention and psychoeducation were also discussed. Issues concerning cultures and religions are also emphasized in the management plans. Conclusion: Biological disaster like SARS and COVID-19 not only has strong impact on mental health in those being infected and their family, friends, and coworkers, but also affect wellbeing in general public. There are evidenced that clear and timely psychoeducation, psychological first aid and psychological debriefing could amileorate negative impact of disaster, thus might also be helpful amid COVID-19 pandemic.